2019
DOI: 10.1111/jace.16674
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and laser operation of Yb:Lu2O3 transparent ceramics from co‐precipitated nano‐powders

Abstract: In this article, 5 at.% Yb:Lu2O3 transparent ceramics were fabricated by vacuum sintering combined with hot isostatic pressing (HIP) posttreatment using co‐precipitated nano‐powders. The influence of precipitant molar ratio, ammonium hydrogen carbonate, to metal ions (AHC/M3+, R value) on the properties of Yb:Lu2O3 precursors and calcined powders was investigated systematically. It was found that the powders with different R value calcined at 1100°C for 4 hours were pure cubic Lu2O3 but the morphologies of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Briefly, the optical quality of 5 at% Yb:Lu 2 O 3 ceramics is improved especially in the short wavelength range compared with the results reported in Ref. [27].…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Briefly, the optical quality of 5 at% Yb:Lu 2 O 3 ceramics is improved especially in the short wavelength range compared with the results reported in Ref. [27].…”
Section: Resultsmentioning
confidence: 48%
“…Figure 5 shows the FESEM micrographs of (a) the prepared precursor and (b) calcined 5 at% Yb:Lu 2 O 3 nano-powder. It can be seen that the amorphous precursor consists of spherical nanogranules and shows weaker agglomeration compared to the flake structural precursors reported in our previous study [27]. The microstructure of the synthesized precursor changes greatly.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The existence of PAA does not affect the crystallite sizes of the powders but does affect the calcinated particle size slightly. As the formed particles are an agglomeration of the crystallites, Liu et al 21 had suggested to use a formula of N = (D BET /D XRD ) 3 to quantitatively describe the dispersity of the synthesized powders. The smaller the N value, the better the dispersity of the powder is.…”
Section: Resultsmentioning
confidence: 99%
“…Since addition of suitable amount of sulfate ions in the coprecipitation process could effectively produce yttria powders with low agglomeration and high sinterability, the method has been widely adopted. [17][18][19][20][21][22] Worth of mentioning that using coprecipitated nanopowders with sulfate ions as the dispersant, Liu et al 21 fabricated 5 at.% Yb:Lu 2 O 3 laser ceramics and achieved laser oscillation of the laser ceramics, Dai et al 19 reported the fabrication of 5 at.% Yb:Sc 2 O 3 laser ceramics, and Xie et al 22 fabricated 5 at.% Eu:Lu 2 O 3 transparent ceramics for X-ray detection. However, we note that there is a serious drawback of using sulfate ions as a dispersant.…”
Section: Introductionmentioning
confidence: 99%